Leticia: A Toolbox for Search Task Deployment, Execution, and User Interaction Logging on Interactive Information Retrieval Studies - Gonzalez-Ibanez, R; Gacitua-Vasquez, D (Elsevier B.V., 2023)
The analysis of search behaviors as proxies of users’ cognitive and affective states – in the context of information seeking – is an active research topic on interactive information retrieval (IIR). This type of research requires specialized tools either to run new studies or to replicate previous ones. While several IIR studies have been conducted over the years, the required tools are not always available, making the replicability of such studies more difficult and expensive. To address this problem, in this article, we introduce LETICIA (simuLated sEarch Task deploy and InteraCtIon cApture platform), an open-source solution designed to deploy study designs, conduct them, and collect various types of data. LETICIA offers ready-to-use functionalities that can be customized to fit researchers’ needs. These include a built-in search engine, a tool to build document collections, an application programming interface (API), a powerful data logger, and a session flow manager. LETICIA aims to be a contribution to the IIR community, offering a flexible yet simple tool to deploy environments to conduct user studies. © 2023 The Author(s)